2016
DOI: 10.1016/j.ejbt.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of Mycobacterium neoaurum 3-ketosteroid-Δ1-dehydrogenase in Corynebacterium crenatum for efficient bioconversion of 4-androstene-3,17-dione to androst-1,4-diene-3,17-dione

Abstract: a b s t r a c tBackground: 3-Ketosteroid-Δ 1 -dehydrogenase (KSDD), a flavoprotein enzyme, catalyzes the bioconversion of 4-androstene-3,17-dione (AD) to androst-1,4-diene-3,17-dione (ADD). To date, there has been no report about characterization of KSDD from Mycobacterium neoaurum strains, which were usually employed to produce AD or ADD by fermentation. Results: In this work, Corynebacterium crenatum was chosen as a new host for heterologous expression of KSDD from M. neoaurum JC-12 after codon optimization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Zhang et al . reported that the highest transformation rate of AD to ADD by M. neoaurum KsdD in Corynebacterium crenatum was about 83.87% after 10 h . Shao et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al . reported that the highest transformation rate of AD to ADD by M. neoaurum KsdD in Corynebacterium crenatum was about 83.87% after 10 h . Shao et al .…”
Section: Resultsmentioning
confidence: 99%
“…However, maximum ADD concentrations (2.66 g L −1 ) were obtained at 21 h during the third fed-batch fermentation process (bioconversion from 18 h to 27 h). Zhang et al reported that the highest transformation rate of AD to ADD by M. neoaurum KsdD in Corynebacterium crenatum was about 83.87% after 10 h. 50 Shao et al reported that ADD conversion rate of M. neoaurum KsdD in E. coli achieved 95% in 36 h using a fed-batch strategy. 37 However, the bioconversion of AD to ADD with A. simplex KsdD-expressing B. subtilis was only 45.3%.…”
Section: Bioconversion Of Steroids By Ksdd4 Resting Cellsmentioning
confidence: 99%
“…P. pastoris expresssion KstD F from Aspergillus fumigatus CICC 40167 is able to transform 1 g L −1 AD to ADD after 4 h of fermentation, however, the cell culture needs a further 6 days to establish [ 20 ]. In addition, KstD1 from M. neoaurum JC-12 has been expressed in C. crenatum , E. coli and B. subtili s to produce ADD from AD [ 22 24 ]. The highest yield (8.76 g L −1 ) was obtained in B. subtili s, with a fed-batch strategy in 50 h, after codon optimization and co-expression with catalase to remove H 2 O 2 toxicity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A B. subtilis, expressing codon-optimized kstD gene from M. neoaurum JC-12, produced 8.76 g L −1 ADD by whole-cell biocatalysis [ 24 ]. Prominently, a KstD overexpressing C. crenatum can transform 83.87% of the AD to ADD [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The only reports related to this issue are the work of Charney et al [6] concerning biotransformations of steroid substrates using Corynebacterium simplex (previously classified as Arthrobacter simplex and Pimelobacter simplex, and currently known as Nocardioides simplex) and the recent work of Zhang et al [7] who used Corynebacterium crenatum as host to express the 3-ketosteroid-∆ 1 -dehydrogenase from Mycobacterium neoaurum to catalyze the bioconversion of 4-androstene-3,17-dione (AD) to androst-1,4-diene-3,17-dione (ADD).…”
Section: Introductionmentioning
confidence: 99%